Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa dalam Berwirausaha - Barkudin Barkudin (Populer: Jurnal Penelitian Mahasiswa, 2025)
Research was conducted to determine the factors that influence students’ interest in entrepreneurship. The methode used is a quantitative method, the research population is students at at Pasim National University in semesters 3 and 4, the research sampel consisted of 86 respondents. The collected data was analyzed using validity, reliability and simpel regression analysis tests. The results of the analysis show that the data meets the validity and reliability test requirements, the results of the partial analysis of the emotional intelligence variable have an influence of 5,221 on interest in entrepreneurship, the family environment has an influence of 4,823 in student interest in entrepreneuship and self efficacy has an impact of 5,882 on student interest in entrepreneuship. This value is greater. From the t table values of 1,663 so that partially each variable has an impact on interest in entrepreneurship, simultaneous analysis there is a significant influence from the variables emotional intelligence, environment family and sel-efficacy towards students’ entrepreneurial interests.